Pengaruh Kompensasi, Motivasi dan Disiplin Kerja Terhadap Kepuasan Kerja Karyawan pada PT Epiroc Southern Asia Balikpapan - Nursella; Syahril Hasan; Tutik Yuliani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The purpose of this study is to determine the Effect of Compensation, Motivation and Work Discipline on Employee Job Satisfaction of PT> Epiroc Southern Asia Balikpapan. Data collection was carried out by distributing a questionnaire with a total of 37 respondents from PT. Epiroc Southern Asia Balikpapan, this research method uses a quantitative method. The sampling technique in this study uses the total sampling technique or census. Statistical tests and data processing were carried out using Partial Least Square (PLS) with the Smart PLS program version 3.0. The results of the study show that the motivation variable has a positive and significant effect on the job satisfaction of employees of PT. Epiroc Southern Asia Balikpapan while the variables of compensation and work discipline have no effect on the job satisfaction of employees of PT. Epiroc Southern Asia Balikpapan.